Endocrine Disruptors in Mediterranean Top Marine Predators - FOSSI, M. C.; CASINI, S.; MARSILI, L. (Environmental Science and Pollution Research - International, 2006)
Background, Aims and Scope. Man-made Endocrine Disruptors (EDs) range across all continents and oceans. Some geographic areas are potentially more threatened than others: one of these is the Mediterranean Sea. Levels of some xenobiotics are much higher here than in other seas and oceans. In this paper we review the final results of a project in which the hypothesis that Mediterranean top predator species (such as large pelagic fish and marine mammals) are potentially at risk due to EDs was investigated. Methods. In a four-year survey on the Mediterranean population of swordfish (Xiphias gladius), the potential toxicological effects of organochlorine compounds (OCs) on specimens of swordfish and tuna fish (Thunnus thynnus thynnus), caught in the spawning seasons from 1999 to 2002 in the Straits of Messina, Sicily (Italy), were investigated using vitellogenin (Vtg), Zona radiata proteins (Zrp), and cytochrome P4501A (CYP1A) activities (EROD, BPMO). Tissues (skin and blubber) were obtained from Stenella coeruleoalba, Tursiops truncatus, Delphinus delphis and Balaenoptera physalus from the western Ligurian Sea, between Corsica and the French-Italian coast, and Ionic Sea using biopsy darts launched with a crossbow. Benzo(α)pyrene monoxigenase (BPMO) activity was mesured in biopsies and cholrinated hydrocarbon levels were detected. Results and Discussion. We illustrate the need to develop and apply sensitive methodological tools, such as biomarkers (Vitellogenin, Zona Radiata proteins and CYP1A activities) for evaluation of toxicological risk in Xiphias gladius and Thunnus thynnus thynnus), and nondestructive biomarkers (CYP1A activities and fibroblast cell culture in skin biopsy), for the hazard assessment of threatened marine mammals species (Stenella coeruleoalba, Tursiops truncatus, Delphinus delphis and Balaenoptera physalus) exposed to EDs. Conclusion. The present research shows that: a) Vtg and Zrp can be used as diagnostic tools for fish stocks hazard assessment in the Mediterranean Sea; b) that CYP1A1 (BPMO) ...